Elevating Cognitive Learning Outcomes via Inquiry Learning Empowered by Digital Web Teaching Materials in Science Education: Meningkatkan Hasil Belajar Kognitif melalui Pembelajaran Inquiry dengan Bantuan Materi Pengajaran Digital Berbasis Web dalam Pendidikan Sains - Sari, Dewi Ratna; Wulandari, Ria (Indonesian Journal of Education Methods Development, 2023)
This study employs a quantitative approach to investigate the impact of an inquiry learning model supported by digital web teaching materials on science learning outcomes among middle school students. The pre-experimental research method with a one-group pretest-posttest design was employed in an experimental class at Muhammadiyah 5 Reinforcement Middle School. Utilizing cognitive learning outcome multiple-choice questions, the study found a significant increase in student learning outcomes, supported by a medium-category average N-Gain score. Paired sample t-test results indicated rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1), with a significance level of 0.00. The tcount (27.043) exceeded ttable (2.056), affirming the efficacy of the inquiry learning model assisted by digital web teaching materials. This study contributes to the understanding of enhancing cognitive science learning outcomes through innovative instructional approaches, highlighting the potential of digital tools to elevate education quality. Highlights: Effective Pedagogical Approach: The study demonstrates the effectiveness of an inquiry-based learning model supported by digital web teaching materials in improving cognitive learning outcomes in science education. Significant Learning Gains: The research reveals a substantial increase in student learning outcomes, with a medium-category average N-Gain score, affirming the positive impact of the instructional intervention. Innovative Educational Tools: This study underscores the potential of integrating digital web teaching materials to enhance the inquiry learning process, providing valuable insights for educators and curriculum developers seeking to optimize science education strategies. Keywords: Inquiry learning, digital web teaching materials, cognitive learning outcomes, science education, middle school.